Policy Alignment Initiatives and Awareness Management Among Third Party Service Provider in a Manufacturing Company - Cabiscuelas, John Christian (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the relationship between policy alignment initiatives and awareness management among third-party service providers in a manufacturing company located in the First Philippine Industrial Park. The research was anchored on Agency Theory and human resource management perspectives, emphasizing how structured alignment of organizational policies influences employee-related awareness, behavior, and coordination within outsourced service arrangements. A quantitative descriptive-correlational research design was employed, involving 134 respondents selected through G*Power sampling estimation. Data were gathered using researcher-made questionnaires validated for reliability and analyzed using frequency distribution, Likert scale interpretation, mean, Pearson correlation coefficient, and regression analysis through SPSS. Findings revealed that the level of policy alignment initiatives among third-party service providers was generally “Initiated,” particularly in terms of goals participation, organizational goals, and employee behavior. Likewise, awareness management was assessed as “Aware,” with motivation, knowledge competence, and collaboration reflecting moderate but developing levels. Statistical analysis further showed a significant and strong positive relationship between policy alignment initiatives and awareness management, indicating that improved alignment of organizational policies is associated with higher levels of awareness among third-party service providers. The null hypothesis was rejected, confirming a significant relationship between the variables. Based on the results, the study concludes that strengthening policy alignment mechanisms enhances awareness management, particularly in external service provider arrangements where compliance and coordination are critical. It is recommended that structured awareness programs, communication systems, and policy reinforcement strategies be implemented to further improve alignment and operational consistency among third-party service providers. In relation to sustainable development, the study supports Sustainable Development Goal (SDG) 8 (Decent Work and Economic Growth) by promoting efficient, ethical, and well-aligned workforce systems in industrial settings. It also aligns with SDG 9 (Industry, Innovation, and Infrastructure) by strengthening organizational processes and improving industrial operational coordination. In terms of sustainability impact, the findings contribute to institutional and governance sustainability by enhancing policy compliance, organizational efficiency, and long-term collaboration between manufacturing firms and outsourced service providers, thereby improving operational stability and workforce accountability.